1998
DOI: 10.1079/bjn19980032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short- and long-term effects of different dietary fats on the hepatic uptake and metabolism of chylomicron remnants in rats

Abstract: The uptake and metabolism of [ ''C]oleate-labelled chylomicron remnants derived from olive oil, maize oil, palm oil, fish oil or butter fat was investigated using perfused livers from rats fed on the corresponding fat-supplemented diet (providing 40 % of the dietary energy) or a low-fat diet for 21 d. The percentage of added ['4C]oleate-labelled remnant removed from the perfusate was similar for livers from rats fed on the fat-supplemented diets irrespective of the type of fat fed, whereas livers from rats fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Little information is available, however, about the effects of dietary fats on the expression of the LRP. In our previous work [19,20,45], we found that feeding rats the corresponding fat in the diet altered the pattern of the differences in the hepatic uptake of chylomicron remnants of varying fatty acid composition. The present results, therefore, suggest that it is possible that these changes may be caused by induction or repression of the LDL receptor and/or the LRP by the various fat‐supplemented diets.…”
Section: Discussionmentioning
confidence: 99%
“…Little information is available, however, about the effects of dietary fats on the expression of the LRP. In our previous work [19,20,45], we found that feeding rats the corresponding fat in the diet altered the pattern of the differences in the hepatic uptake of chylomicron remnants of varying fatty acid composition. The present results, therefore, suggest that it is possible that these changes may be caused by induction or repression of the LDL receptor and/or the LRP by the various fat‐supplemented diets.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing carotenoid absorption when dispersed in PUFA was reported in rat (Clark et al, 2000). Moreover, in the rat, dietary lipids of plant origin, in contrast to those of animal origin, promote the accumulation of β-carotene in plasma (Alam et al, 1989) by influencing chilomicron metabolism (Lambert et al, 1998). The reason for this is not fully understood.…”
Section: Parametermentioning
confidence: 99%
“…Moreover, Rukkwamsuk et al (2000) have reported that the profile of fatty acids (FA) within the liver is dramatically changed when intracellular adipocyte lipolysis increases, thus changing the composition of fatty acids reaching the liver. Other experiments have demonstrated that dietary fat induces metabolic changes in laboratory rodents such as increased peroxisomal and mitochondrial β-oxidation of FA (Kumamoto and Ide, 1998), decreased esterification of FA (Malewiak et al, 1988), and altered profiles and clearance of plasma lipoproteins (Lambert et al, 1998). Most of these changes in lipid metabolism of rodents were observed during starvation or negative energy balance, which would be similar to the negative energy balance occurring after calving.…”
Section: Introductionmentioning
confidence: 96%